G Protein-Coupled Receptors : Structure, Signaling, and Physiology / [electronic resource] - Siehler, Sandra; Milligan, Graeme (Cambridge : Cambridge University Press, 2010)
Provides a comprehensive overview of recent discoveries and current understandings of G protein-coupled receptors (GPCRs). Recent advances include the first mammalian non-rhodopsin GPCR structures and reconstitution of purified GPCRs into membrane discs for defined studies, novel signaling features including oligomerization, and advances in understanding the complex ligand pharmacology and physiology of GPCRs, in new assay technologies and drug targeting. The authors take time to detail the importance of the pathophysiological function and drug targeting of GPCRs, specifically gb(B-adrenoceptors in cardiovascular and respiratory diseases, metabotropic glutamate receptors in CNS disorders, S1P receptors in the immune system, and Wnt/Frizzled receptors in osteoporosis. This book will be invaluable to researchers and graduate students in academia and industry who are interested in the GPCR field.s
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: G proteins; Cell receptors; Cellular signal transduction; Drug Delivery Systems